Bloom of the Flower Dragon - West, Tracey, 1965-; Howells, Graham (New York, NY : Branches/Scholastic Inc., 2022)
Drake and the other Dragon Masters help Wildroot, a Flower Dragon whose home is in danger, find his Dragon Master Oskar after Oskar's identity is revealed to them by the Dragon Stone.
Ages 6-8.
Grades 2-3.
580L
Decoding demand: 79 (high) Semantic demand: 95 (very high) Syntactic demand: 80 (high) Structure demand: 85 (very high)
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Dragons -- Fiction; Magic -- Fiction; Wizards -- Fiction; Adventure and adventurers -- Fiction; Fantasy fiction; Action and adventure fiction